Landscape design for residential area - Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zen, Ismawi (Springer, 2018)
Landscape design for residential area should be favorable for the ambience of ecological environment and for the enhancement of both the local climate of a residential and the environmental quality of life. The paper provides information that will enable people toward a better understanding of landscape design for residential. A good-quality residential area can be highlighted as an important issue in creating a sustainable living environment. It begins by describing landscape focuses on landscape design in residential development. It also reviews the issues related to the residential landscape design and residential landscape for green neighborhood in order to obtain a clearer and better picture of the basic needs of landscape for residential developments.